Pengamalan Nilai-Nilai Islam Dalam Kehidupan Bermasyarakat Di Desa Lumbang, Kec. Lumbang, Kab. Probolinggo - Aswat, Hazarul (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Basically, human life cannot be separated from rules, with the existence of real forms of religious activities, it is hoped that it will have a positive impact on daily life in society to understand what can be done and what cannot be done with the barometer of Islamic teachings that are relevant at all times. Focus on devotion, how to convey the message of da'wah with current developments without ignoring religious values. And the goal of service is a concrete manifestation of the practice of Islamic values. The research method used, descriptive qualitative, is a form of social and religious service related to the practice of Islamic teachings. As a result of the service, the practice of instilling Islamic values ​​in Lumbang Village, Lumbang District, Probolinggo Regency has had a positive impact on people's lives, as well as the practice of Islamic values ​​in daily life, this activity has become an opportunity to strengthen friendship between fellow citizens. , and the active role of the community in these activities makes them understand how important religious teachings are in the continuity of life in the current generation and beyond. With religious activities, it is hoped that they can make a better contribution to religious life for the Islamic ummah and society in general.